Adaptation and Continuity: Banjar Organizations and the Preservation of Balinese Ethnic Identity among Transmigrant Communities in Lampung, Indonesia - Intan Fitri Meutia; Haruya Kagami (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
This study aims to analyze how Balinese transmigrants in Lampung sustain their ethnic identity through community organization, focusing on the adaptation and function of banjar organization in both enclave villages and urban settings. Employing qualitative field methods including interviews, surveys, and observation in Balinuraga village and Bandar Lampung city, the research contrasts the preservation strategies of traditional banjar institutions. The findings reveal that in rural enclaves, banjar structures closely replicate customary institutions from Bali, fostering strong ethnic, religious, and social cohesion. In contrast, urban banjar associations demonstrate greater inclusivity, accommodating inter-religious and inter-ethnic members and emphasizing cultural activities to reinforce identity. The study concludes that community organization remains crucial for ethnic continuity, but adaptation is required in diverse urban environments. Its novelty lies in the empirical comparison of banjar models across enclave and multicultural contexts, revealing unique mechanisms for maintaining identity. Further research should address generational change and the sustainability of banjar structures amid ongoing urbanization and social integration.